anonymous
  • anonymous
y - 2x = 3 3x - 2y = 5 solve by substitution. help? :/
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
so basically, in substitution you want to solve for one variable in one of the equations
anonymous
  • anonymous
x=1 and y=5
anonymous
  • anonymous
so for example, y - 2x = 3 becomes y = 2x+3. then substitute y in the second equation as 2x+3 so 3x - 2y = 5 becomes 3x - 2(2x+3) = 5

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Solve for x. Then plug in the answer from x to find y. You should get anirud's answer
anonymous
  • anonymous
Multiply The Equation 2x-y=3 with 2 and Assume it as Equation One and Take 3x-2y=5 as Equation 2 and Subtract 1-2 And Eliminate The y term and then U will Get The Value of x... Then Put the value of x in anyone of the Two Equations and U will get y
anonymous
  • anonymous
You might want to make a note of this one: Whenever they ask you TO SOLVE WITH SUBSTITUTION: Either of the 2 equations, check which one looks simpler: y - 2x = 3 3x - 2y = 5 Wouldn't you say equation 1 looks more simple? :) So, just take the value y in terms of x: y = 3 + 2x. Then put the value of y in the second equation, so we have: 3x-2(3+2x) = 5 3x -6 -4x=5 -x -6=5 Take -x to the other side to get x, and bring 5 to the other side to get -5, -6-5=x -11=x. This is our first answer, let us substitute the value of x in equation 1. y-2(-11)=3 y+22=3 y=3-22 y=-19 So now we have the answer as: x=-11 and y=-19. Please let me know if you have any more doubts about this kind of question or anything else, I will try to explain as clearly as I can. :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.